Isorhamnetin Inhibits Proliferation and Invasion and Induces Apoptosis through the Modulation of Peroxisome Proliferator-activated Receptor [gamma] Activation Pathway in Gastric Cancer - Ramachandran, L.; Manu, K.; Shunmugam, M.; Feng, L.; Siveen, K.; Vali, S.; Kapoor, S.; Abbasi, T.; Surana, R.; Smoot, D.; Ashktorab, H.; Tan, P.; et al. (The American Society for Biochemistry and Molecular Biology Inc, 2012)
Gastric cancer (GC) is a lethal malignancy and the second most common cause of cancer-related deaths. Although treatment options such as chemotherapy, radiotherapy, and surgery have led to a decline in the mortality rate due to GC, chemoresistance remains as one of the major causes for poor prognosis and high recurrence rate. In this study, we investigated the potential effects of isorhamnetin (IH), a 3-O-methylated metabolite of quercetin on the peroxisome proliferator-activated receptor (PPAR-) signaling cascade using proteomics technology platform, GC cell lines, and xenograft mice model. We observed that IH exerted a strong antiproliferative effect and increased cytotoxicity in combination with chemotherapeutic drugs. IH also inhibited the migratory/invasive properties of GC cells, which could be reversed in the presence of PPAR- inhibitor. We found that IH increased PPAR- activity and modulated the expression of PPAR- regulated genes inGC cells. Also, the increase in PPAR- activity was reversed in the presence of PPAR--specific inhibitor and a mutated PPAR- dominant negative plasmid, supporting our hypothesis that IH can act as a ligand of PPAR-. Using molecular docking analysis, we demonstrate that IH formed interactions with seven polar residues and six nonpolar residues within the ligand-binding pocket of PPAR- that are reported to be critical for its activity and could competitively bind to PPAR-. IH significantly increased the expression of PPAR- in tumor tissues obtained from xenograft model of GC. Overall, our findings clearly indicate that antitumor effects of IH may be mediated through modulation of the PPAR- activation pathway in GC.